2013
DOI: 10.1186/1475-2859-12-92
|View full text |Cite
|
Sign up to set email alerts
|

L (+)-lactic acid production by pellet-form Rhizopus oryzae NRRL 395on biodiesel crude glycerol

Abstract: BackgroundGiven its availability and low price, glycerol derived from biodiesel industry has become an ideal feedstock for the production of fuels and chemicals. A solution to reduce the negative environmental problems and the cost of biodiesel is to use crude glycerol as carbon source for microbial growth media in order to produce valuable organic chemicals. In the present paper, crude glycerol was used as carbon substrate for production of L (+)-lactic acid using pelletized fungus R. oryzae NRRL 395 on batch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
(31 reference statements)
1
29
0
Order By: Relevance
“…Moreover, different compositions of crude glycerol affect several fermentative productions (9). Several papers also reported the conversions of crude glycerol derived from a biodiesel production to lactic acid (13,30). Therefore, the effect of crude glycerol on fermentation by strain QU 11 must be examined, in order to determine its applicability to industrial lactic acid production.…”
Section: Effect Of Ph Control and Fed-batch Fermentation On Lactic Acmentioning
confidence: 98%
“…Moreover, different compositions of crude glycerol affect several fermentative productions (9). Several papers also reported the conversions of crude glycerol derived from a biodiesel production to lactic acid (13,30). Therefore, the effect of crude glycerol on fermentation by strain QU 11 must be examined, in order to determine its applicability to industrial lactic acid production.…”
Section: Effect Of Ph Control and Fed-batch Fermentation On Lactic Acmentioning
confidence: 98%
“…Metabolic engineering of the strain by deleting the alcohol dehydrogenase and malate dehydrogenase genes moved the metabolic flux to LA formation. R. oryzae NRRL 395 produced 140 g/l LA on potato hydrolysate (Liu et al, 2008) and 48 g/l LA from 75 g/l glycerol enriched with 25 g/l Lucerne green juice and inorganic nutrients (Vodnar et al, 2013). However, a drawback of filamentous fungi is their fast growth in media containing nitrogen sources producing predominantly chitin instead of LA.…”
Section: Lactic Acid Production By Filamentous Fungimentioning
confidence: 99%
“…Recently, it was reported that metabolically engineered E. coli produced up to 50 g liter Ϫ1 L-lactate from crude glycerol, with a yield of 93% (36), and the Rhizopus oryzae wild-type strain could produce 48 g liter Ϫ1 L-lactate from 75 g liter Ϫ1 crude glycerol in the presence of supplemental nutrients (37). In contrast, E. faecalis ⌬pfl (ldhL1 ϩ ) could convert 300 mM (27 g liter Ϫ1 ) crude glycerol to L-lactate with a yield of Ͼ99%.…”
Section: Discussionmentioning
confidence: 99%